2010
DOI: 10.1128/aem.00924-09
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal Diversity and Distribution along Thermal and Geochemical Gradients in Hydrothermal Sediments at the Yonaguni Knoll IV Hydrothermal Field in the Southern Okinawa Trough

Abstract: Deep-sea hydrothermal activity results in diverse physical and chemical environments for the resident microbial communities. Using cultivation techniques and culture-independent molecular analyses, diverse lineages of archaea and bacteria have so far been observed from chimney structures, retrieved in situ colonization systems settled in or on the hydrothermal conduit, microbial mats, sediments, and chemosynthetic macrofaunal bodies (19,35,62). Especially in the domain Archaea, most of lineages derived from hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 72 publications
3
88
0
Order By: Relevance
“…They were also detected as the predominant population (99% of the total archaeal sequences) in the near-surface sediment at 1 mbsf in Hole C0013B, which is the only sample containing detectable 16S rRNA genes at Site C0013 (data not shown). The HWCGIV sequences have previously been reported in deep-sea hydrothermal vent habitats (Schrenk et al, 2003;Nunoura et al, 2010;Yoshida-Takashima et al, 2012) and in a hightemperature zone at 141.1 mbsf at Site C0017 (Yanagawa et al, 2014).…”
Section: S Rrna Gene Community Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…They were also detected as the predominant population (99% of the total archaeal sequences) in the near-surface sediment at 1 mbsf in Hole C0013B, which is the only sample containing detectable 16S rRNA genes at Site C0013 (data not shown). The HWCGIV sequences have previously been reported in deep-sea hydrothermal vent habitats (Schrenk et al, 2003;Nunoura et al, 2010;Yoshida-Takashima et al, 2012) and in a hightemperature zone at 141.1 mbsf at Site C0017 (Yanagawa et al, 2014).…”
Section: S Rrna Gene Community Structuresmentioning
confidence: 99%
“…In this study, all of the pore-water geochemical analyses, metabolic activity measurements and cellular and molecular microbial community analyses indicated the occurrence of functionally active microbial communities dominated by AOM populations in the relatively shallow subseafloor habitats down to 15.8 mbsf in Hole C0014G. Several studies have examined the abundance, phylogenetic diversity and function of AOM populations associated with seafloor hydrothermal activity in the Guaymas Basin and Yonaguni Knoll IV fields (Teske et al, 2002;Nunoura et al, 2010;Yanagawa et al, 2013a;Dowell et al, 2016). Because these investigations have focused on the shallow sediments just beneath the seafloor, where the diffusive mixing of hydrothermal fluids and seawater likely characterizes the geochemical environments, there remains a lack of knowledge on the subseafloor AOM communities associated with hydrogeologically controlled advection and the partitioning and mixing processes of hydrothermal fluids and infiltrated seawater near deep-sea vents.…”
Section: Synthesis and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides their high CO 2 content, the hydrothermal fluids exhibit a wide variation in gas composition including H 2 , CH 4 , H 2 S and NH 3 . Previous studies have focussed on the distribution of bacterial and archaeal communities of the Yonaguni Knoll IV hydrothermal sediments and overlying bottom waters (Inagaki et al, 2006;Yanagawa et al, 2012;Nunoura et al, 2010). Here we have investigated the biogeochemistry of the CO 2 vented sediments, focussing on the distribution of microbial aerobic and anaerobic respiration pathways.…”
Section: De Beer Et Al: Biogeochemistry Of Deep-sea Co 2 Ventsmentioning
confidence: 99%
“…In particular, reduced compounds such as H 2 , CH 4 , HS À , and Fe 2+ are not only essential energy sources for chemolithotrophs but also factors that control the composition and density of the microbial community. Previous studies have investigated habitat components, for example, the boundary zone (interface) between hydrothermal fluid and ambient seawater, including low-temperature diffusive flow (Holden et al 1998;Huber et al 2002Huber et al , 2003Perner et al 2007), chimney structures (Schrenk et al 2003;Takai et al 2001), and hydrothermal sediments (Nunoura et al 2010;Teske et al 2002;Yanagawa et al 2013). These studies demonstrated the prevalence of Gammaproteobacteria, Deltaproteobacteria, Epsilonproteobacteria, Bacteroidetes, Firmicutes, and various candidate divisions in the hydrothermal system.…”
Section: Introductionmentioning
confidence: 99%